Medicinal and Aromatic Plants of the World Scientific, Production, Commercial and Utilization Aspects - Máthé, Ákos (Medicinal and Aromatic Plants of the World, 2015)
Medicinal and aromatic plants (MAPs) have accompanied mankind from its very early beginnings. Their utilization has co-evolved with homo sapiens itself. Evolution has brought about a profound increase in our scientific knowledge about these species, so that, to date, they find utilization in many facets of our life (eg. pharmaceutical products, feed- and food additives, cosmetics, etc.). Remarkably today, despite the new renaissance of MAPs usage, ca. 80 % of the world's population relies upon natural substances of plant origin, with most of these botanicals sourced from the wild state. This huge increase in demand has put an unparalleled large burden on the natural resources of MAPs endangering their existence. The first volume of the series Medicinal Plants of the World, will briefly summarize the most essential current scientific knowledge about the sustainable sourcing of botanicals from both wild-crafting and cultivation. In these 21 chapters, eminent researchers of the topic will summarize latest scientific knowledge from the versatile and most varied scientific disciplines involved: botany, phytochemistry, plant breeding, biotechnology, agrotechnology, mechanization and economics. Individual chapters will deal with the essentials of phytomedical utilization, as well as utilization in the form of animal feed-additives. The volume concludes with a chapter on the poisonous MAPs in our homes, offices and modern everyday environments. The aim of this volume is to offer basic scientific information on MAPs. It will also enable readers of subsequent volumes to digest and interpret the other volumes in the series, that will deal with important and characteristic wild-crafted and cultivated MAPs of the different geographic and climatic regions of the world.  Thus, the series is meant to be a storehouse of up-to-date information on our global wealth of medicinal and aromatic plants on the basis of which MAPs will be collected, cultivated, traded and utilized in a sustainable way.